Analysis of Risk Factors of Workplace Accidents in Construction Workers In The Tallasa City Area - Datu, Hesty; S. Russeng, Syamsiar; Thamrin, Yahya (Journal of Neonatal Surgery, 2025)
Background: Construction workers are at high risk of experiencing work accidents due to the characteristics of heavy and complex work. Various individual and work environment factors can influence the occurrence of accidents . Objective: This study aims to analyze the risk factors for work accidents in construction workers in the Tallasa City area . Method: The design of this study was a case control with a quantitative approach. The sample consisted of 70 respondents (35 cases and 35 controls), with matching based on gender and type of employment. Data were analyzed using the chi-square test, odds ratio (OR), and multiple logistic regression . Results: The results of the bivariate analysis showed that the variables significantly associated with work accidents were length of service (OR=5.073; p=0.002), education level (OR=3.039; p=0.030), training history (OR=4.463; p=0.003), working hours (OR=3.524; p=0.012), and use of PPE (OR=3.864; p=0.007). Marital status did not show a significant relationship (p=0.131). The results of the multivariate analysis showed that length of service was the most influential variable (OR=4.627; 95% CI=1.604–13.348; p=0.005). Conclusion: Working period ≤ 3 years significantly increases the risk of work accidents. Therefore, special training, mentoring, and supervision for new workers are very important to reduce the number of work accidents.